Protective Effect of Lantana camara Methanolic Leaf Extract Against Acetaminophen-induced Liver Injury in Male Albino Rats - Hyelda Stephen; Balaraba Bello (Mazandaran University of Medical Sciences, 2024)
Background and Objectives: Lantana camara is used traditionally against liver ailments, but scientific evidence for its hepatoprotective effects is limited. This study evaluates the hepatoprotective effect of methanolic leaf extract of L. camara against acetaminophen-(APAP) induced hepatotoxicity in a rat model.  Methods: Phytochemical analysis revealed the presence of phenolics (5.03%), alkaloids (4.30%), saponins (6.14%), tannins (3.81%) and flavonoids (3.54%) in the extract. Methanolic leaf extract of L. camara was administered orally to rats at 100, 300 and 500 mg/kg doses for 5 days before APAP challenge at 750 mg/kg. Serum liver enzymes, proteins, bilirubin and histopathology were assessed to determine the extent of liver injury and protection.  Results: APAP administration caused significant (P<0.05) elevation of serum aspartate transaminase (AST) (89.57±6.90 U/L), alanine transaminase (ALT) (35.61±0.81 U/L), alkaline phosphatase (ALP) (124.90±1.94 U/L), and bilirubin levels along with a reduction of total protein (57.77±0.73 g/L) and albumin levels (25.21±1.08 g/L). It also induced severe hepatocellular necrosis and inflammation. Pretreatment with 300 mg/kg extract dose conferred optimal protection by normalizing enzyme activities (AST: 58.61±2.88 U/L, ALT: 23.57±1.71 U/L, ALP: 92.99±9.87 U/L) and liver function biomarkers (total protein: 80.42±1.72 g/L, albumin: 27.79±1.91 g/L). It also preserved near-normal liver tissue architecture with minimal necrosis, indicating its antioxidant and membrane-stabilizing properties. Conclusion: The findings validate the ethnomedicinal use of L. camara and indicate its potential for development as an affordable therapy for APAP overdose liver damage.